EFL Students’ Voices: The Role of YouTube in Developing English Competences - Inda Nofrika (Universitas Muhammadiyah Yogyakarta, 2019)
YouTube is one of the most visited video-sharing platforms in the world. On YouTube, students can watch many kinds of videos. This research explored the types of videos often watched by English as A Foreign Language (EFL) students in a private university in Yogyakarta.Additionally, the aspects of students’ English competence got improvement by watching YouTube videos. The researcher employed a descriptive qualitative research design in this study. Four seniors of an English Language Education Department (ELED) in one private Islamic university in Yogyakarta participated in this study. The findings of the study indicated that there were three categories of YouTube videos often watched by students, such as art and humanities, vlogs, and social sciences. Art and humanities videos consist of a music video or lyric video, film, talks, sitcom, and talk show. Vlogs include food vlog, review video, beauty vlog, haul vlog, and DIY videos. Social sciences contain simulation and educational videos.To summarize, the students watch YouTube based on their interests. The result also revealed the aspects of English improved through watching YouTube videos. They are speaking skills, listening skills, pronunciation, vocabulary, and grammar.